2023
DOI: 10.1186/s13395-022-00312-w
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: investigation of metabolic changes and its associated mechanisms

Abstract: Background Sarcopenia is one of the most predominant musculoskeletal diseases of the elderly, defined as age-related progressive and generalized loss of muscle mass with a simultaneous reduction in muscle strength and/or function. Using metabolomics, we aimed to examine the association between sarcopenia and the plasma metabolic profile of sarcopenic patients, measured using a targeted HPLC-MS/MS platform. Methods Plasma samples from 22 (17 men) hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(58 reference statements)
2
2
0
Order By: Relevance
“…acids and dicarboxylic acid carnitines as key variables associated with disease severity in patients with sarcopenia [42]. These findings combined with our results suggest a potential link between sarcopenia and dysregulation of peroxisomal β-oxidation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…acids and dicarboxylic acid carnitines as key variables associated with disease severity in patients with sarcopenia [42]. These findings combined with our results suggest a potential link between sarcopenia and dysregulation of peroxisomal β-oxidation.…”
Section: Discussionsupporting
confidence: 81%
“…β-oxidation of very long-chain fatty acids (VLC-FA) and subsequent production of dicarboxylic acid carnitines also occur in the peroxisome [41]. Metabolomic studies identified very long-chain fatty acids and dicarboxylic acid carnitines as key variables associated with disease severity in patients with sarcopenia [42]. These findings combined with our results suggest a potential link between sarcopenia and dysregulation of peroxisomal β-oxidation.…”
Section: Discussionsupporting
confidence: 66%
“…Acylcarnitine, disrupting peroxisomal or mitochondrial oxidation processes [ 29 ], also plays a part in mitochondrial function, whose dysregulation is highly involved in the pathological loss of skeletal muscle mass and function in the elderly [ 30 ]. 3-dehydrocarnitine is an intermediate in carnitine degradation, and carnitine has been linked to muscle mass or physical weakness [ 31 , 32 ], which plays a crucial role in energy metabolism and mediates the pathway of fatty acid oxidation in the mitochondria [ 33 ]. However, these observational results are limited in determining causal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine and acyl-carnitines were analyzed with an in-house method based on the LC–MS/MS method by Giesbertz et al [ 35 ] and are described by Marques et al [ 36 ].…”
Section: Methodsmentioning
confidence: 99%